Recent Developments in the Conversion of Synthesis Gas to Short‐Chain Alcohols over Cu‐Co‐Based Catalysts. Issue 10 (9th July 2018) - Schmidt, Stefan; Göbel, Christoph; Nebel, Janine; Wiesmann, Thomas; Hamel, Christian; Reinsdorf, Arne; Wolf, Dorit; Gehrmann, Stefan; Tenhumberg, Nils; Muhler, Martin; Kaluza, Stefan
Abstract: Cu‐Co‐based catalysts provide promising systems for higher alcohol synthesis (HAS) due to a synergistic dual‐site mechanism. Bimetallic Cu‐Co (alloy) nanoparticles are assumed to be the active sites, but cobalt carbide (Co2 C) forming under reaction conditions also seems to influence the formation of C2+ OH. Na‐doped Co‐modified Cu/ZnO/Al2 O3 is applied as benchmark catalyst within the Carbon2Chem® subproject L4 providing suitable performance in terms of CO conversion and C2+ OH selectivity. However, further optimization is required in order to develop an economically viable HAS process. Abstract : The conversion of synthesis gas into short‐chain alcohols is considered a promising industrial process. Multimetallic systems based on Cu and Co have already been identified as suitable catalysts for the reaction. However, the nature of the active sites is still not clear, and further improvement in terms of activity and selectivity is required.